2002
DOI: 10.1007/s11664-002-0169-5
|View full text |Cite
|
Sign up to set email alerts
|

Electron backscattering diffraction investigation of focused ion beam surfaces

Abstract: A focused ion beam (FIB) instrument has been used to mill surfaces in singlecrystal Si and single-crystal Cu for subsequent electron backscattering diffraction (EBSD) analysis. The FIB cuts were performed using a 30 keV and a 5 keV Ga ϩ ion beam at a stage tilt of 20°to provide a readily obtainable 70°surface for direct EBSD investigation in a scanning electron microscope (SEM). The quality of the patterns is related to the amount of FIB damage induced in the Cu and Si. These or similar methods should be direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 13 publications
2
69
1
Order By: Relevance
“…The simulation result supports the results of prior works (Matteson et al, 2002;Michael & Kotula, 2008) that high-accelerating FIB milling voltage can induce damage deeper than low voltage. Figure 8 shows a band contrast image of the STN99 sample where the surface has been milled with stripes of different milling conditions.…”
Section: Effect Of Fib Voltagesupporting
confidence: 88%
See 1 more Smart Citation
“…The simulation result supports the results of prior works (Matteson et al, 2002;Michael & Kotula, 2008) that high-accelerating FIB milling voltage can induce damage deeper than low voltage. Figure 8 shows a band contrast image of the STN99 sample where the surface has been milled with stripes of different milling conditions.…”
Section: Effect Of Fib Voltagesupporting
confidence: 88%
“…The purpose of this study is to investigate a suitable FIB voltage to perform FIB polishing during automated 3D-EBSD data collection of STN-and YSZbased materials. A 5 kV FIB voltage was selected in this study as improvements in EBSP quality after low voltage milling in metals have been reported (Matteson et al, 2002;Michael & Kotula, 2008). Surface preparation using 2 kV FIB polishing was also reported to give a better EBSP quality (Michael & Giannuzzi, 2007); however, due to FIB alignment issues and the slow milling rate, 2 kV polishing was not investigated.…”
Section: Effect Of Fib Voltagementioning
confidence: 99%
“…An FEI NOVA200 dual-beam system was used for the preparation of the gold wire samples. Sample preparation through FIB milling results in highquality EBSD band contrast [17,18]. The ion source is liquid Ga metal and ion milling currents ranging from 50 pA to 3 nA and a constant accelerating voltage of 30 kV were used for the gold wire milling.…”
Section: Methodsmentioning
confidence: 99%
“…Irradiating a material surface in grazing incidence allows the preparation of smooth surfaces that show little radiation damage. [10][11][12] This technique has been used extensively for the preparation of transmission electron microscopy (TEM) samples, as well as for the preparation of flat surfaces for metallographic investigations. Through the sputtering of subsequent parallel surfaces, serial sections can be created that may be separated by precisely defined distances of some 10 nm up to several microns.…”
Section: B Tomography By Serial Sectioningmentioning
confidence: 99%